Converting the problematic CO2 into valuable products – Functional characterization of a bacterial formate dehydrogenase to develop green biocatalytic systems for CO2 reduction - Amador , André (2024)
CO2-driven climate change is a serious threat to human societies and the survival of numerous species. Reducing atmospheric CO2 is, therefore, urgent. This constitutes an exceptionally difficult task, but also an opportunity, as CO2 can be repurposed to produce added-value compounds. Yet, to avoid further exacerbating the planet crisis, CO2 conversion has to be accomplished under "green", environmentally friendly conditions and enzymatic-based approaches are ideal for this purpose. This Dissertation focused on the study of the periplasmic Desulfovibrio desulfuricans formate dehydrogenase (DdFDH), an enzyme that was previously shown to be a very efficient CO2 reducer. Herein, the DdFDH-catalyzed formate oxidation was kinetically characterized using three artificial electron acceptors. Benzyl viologen (BV) was identified as the compound exhibiting the most favorable electron transfer with FDH (K_m^(app formate) = 44.4  2.01 M and k_cat^(app formate) = 321  1.73 s-1). Methyl viologen (MV) was found to be a DdFDH less favorable redox partner and, unexpectedly, to follow a "ternary-complex" kinetic mechanism (V_max^formate = 37.3  0.6 M/min, K_m^formate = 44.7  1.5 M, K_i^formate = 232  27.6M and K_m^(' MV) = 384  43 M). Dichlorophenolindophenol was studied with DdFDH for the first time and its catalytic performance was also poorer than the BV one (similar K_m^(app formate) = 42.1  4.1 M, but lower V_max^(app formate) = 12.8  0.1 M/min). Additionally, it was demonstrated that DdFDH cannot reduce nitrate, being instead inhibited by it (mixed-type inhibition; K_ic^nitrate = 1.55 ± 0.05 mM and K_iu^nitrate = 47.9 ± 1.70 mM). The elusive DdFDH activation mechanism was revisited to study the performance of different reductants, as well as of several thiol reagents. Dithiothreitol (11 μM), cysteine (20 μM) and cysteamine (100 μM) activated DdFDH, with β-mercaptoethanol (500 μM) being the least effective thiol. Surprisingly, the "bulky" GSH (70 μM) and CoA (50 μM) also fully activated DdFDH, suggesting that the thiol role in the activation is centered on the enzyme surface. A computed structural model of DdFDH was generated to shed some light on the enzyme catalysis and its activation mechanism. By enhancing our understanding of DdFDH catalysis, this work is contributing to the development of biotechnological devices for CO2 utilization.